Clinical Characteristics and Prognosis of Gastrointestinal Metastases in Solid Tumor Patients: A Retrospective Study and Review of Literatures - Li Lin; Xiangyi Wang; Chuanhao Tang; Jun Liang (Analytical Cellular Pathology)
Background. According to the literature and our experience, patients with gastrointestinal metastases are relatively rare. Numerous case reports and literature reviews have been reported. We present one of the larger case series of gastrointestinal metastases. Objectives. To explore the clinical characteristics and prognosis of patients with gastrointestinal tract metastases, which are rare metastatic sites. Methods. Patients with gastrointestinal metastases in the setting of stage IV primary carcinomas treated at Beijing Ditan Hospital and Peking University International Hospital from November 1992 to August 2017 were included in this study. The diagnosis of gastrointestinal tract metastases was based on histopathology. Results. 30 patients (median age 56 years, 56.7% female) were included. The most common primary carcinomas associated with gastrointestinal metastases were breast (11 patients, 36.7%), stomach (9 patients, 30.0%), and lung (4 patients, 13.3%) cancer. The major pathological types were adenocarcinoma (16 patients, 53.3%) and ductal carcinoma (9 patients, 30.0%). Ten patients (33.3%) underwent local gastrointestinal treatment, and 20 patients (66.7%) underwent nonlocal treatment (involving chemotherapy alone or best supportive care). For breast cancer patients and gastric cancer patients who underwent local therapy, a significant survival advantage was observed (p=0.001 and p=0.012, respectively). The presence of other common metastases was identified as an independent poor prognostic factor through multivariate analysis with a HR (hazard ratio) of survival of 0.182 (95% confidence interval (CI) 0.11-0.523, p=0.031). Conclusion. Gastrointestinal metastases are most frequently from breast invasive ductal carcinoma. The presentation of other common metastases with gastrointestinal metastasis indicates poor prognosis, and selected patients may benefit from surgical intervention.